2020
DOI: 10.1111/cns.13451
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota interacts with intrinsic brain activity of patients with amnestic mild cognitive impairment

Abstract: Aims To explore the potential relationships among gut microbiota (GM), local brain spontaneous activity, and neuropsychological characteristics in amnestic mild cognitive impairment (aMCI) patients. Methods Twenty aMCI and 22 healthy control (HC) subjects were recruited. The GM composition was determined by 16S ribosomal RNA gene sequencing. Resting‐state functional magnetic resonance imaging scans were performed, and fractional amplitude of low‐frequency fluctuations (fALFF) was calculated across different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 48 publications
4
61
1
Order By: Relevance
“…We speculate that this may be due to the relatively slight pathological changes in the early stage of the disease, which leads to the insensitivity of the local functional indicators to reflect the nerve damage. A recent study on the interaction between gut microbiota with the local brain activity of amnestic MCI patients found different interaction types in different sub‐bands 72 . This study supports our results.…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that this may be due to the relatively slight pathological changes in the early stage of the disease, which leads to the insensitivity of the local functional indicators to reflect the nerve damage. A recent study on the interaction between gut microbiota with the local brain activity of amnestic MCI patients found different interaction types in different sub‐bands 72 . This study supports our results.…”
Section: Discussionsupporting
confidence: 92%
“…Lachnospiraceae plays an important role in modulating GI motility (Yano et al, 2015 ). It is found that Lachnospiraceae dynamically changed with age and positively correlated with anxiety and cognition levels (Duan et al, 2019 ; Tengeler et al, 2020 ; Liu et al, 2021 ). The abundance of Lachnospiraceae is significantly decreased in the age-matched PSCI patients (Ling et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gut microbiota is neither the key factor in stroke and AD pathology nor the only treatment target for CNS diseases. Gut dysbiosis is the consequence of CNS diseases possibly due to the gut‐brain axis that worsens cognitive impairment, 99–101 and it is one of many potent treatment targets that may regulate neuroinflammation and reduce stroke outcomes. Elucidating the key role of gut microbiomes in CNS disease pathology may elucidate new potential targeted candidates for stroke therapy.…”
Section: Resultsmentioning
confidence: 99%